Limosilactobacillus fermentum prevents gut-kidney oxidative damage and the rise in blood pressure in male rat offspring exposed to a maternal high-fat diet. (19th December 2022) - do Nascimento, Luciana Caroline Paulino; de Souza, Evandro Leite; de Luna Freire, Micaelle Oliveira; de Andrade Braga, Valdir; de Albuqeurque, Thatyane Mariano Rodrigues; Lagranha, Cláudia Jacques; de Brito Alves, José Luiz
Abstract: Oxidative stress along the gut-kidney axis is a risk factor for developing arterial hypertension in offspring from dams fed a high-fat diet. Considering the antioxidant capacity of probiotic strains, this study evaluated the effects of a daily multistrain formulation with Limosilactobacillus fermentum 139, 263, and 296 on blood pressure (BP), renal function, and oxidative stress and along the gut-kidney axis in male offspring from dams fed a high-fat high-cholesterol (HFHC) diet during pregnancy and lactation. Dams were fed a diet control or HFHC diet during pregnancy and lactation. At 100 days of age, part of the male offspring from dams fed a HFHC diet received Limosilactobacillus fermentum formulation for 4 weeks (HFHC + Lf) daily. After the 4-week intervention, BP (tail-cuff plethysmography) and urinary and biochemical variables were measured. In addition, malondialdehyde levels, enzymatic activities of superoxide dismutase, catalase, glutathione-S-transferase, and nonenzymatic antioxidant defense (thiols content) were measured in the colon and renal cortex. Male offspring from dams fed a HFHC had increased blood pressure, impaired renal function, and oxidative stress along the gut-kidney axis. Administration of Limosilactobacillus fermentum reduced systolic, diastolic, and mean blood pressure levels and alleviated renal function impairment and oxidative stress along the gut-kidney axis in male offspring from dams fed a HFHC diet. Administration of Limosilactobacillus fermentum formulation attenuated programmed hypertension in the HFHC group through oxidative stress modulation along the gut-kidney axis.